2013
DOI: 10.4314/jab.v69i0.95072
|View full text |Cite
|
Sign up to set email alerts
|

Impacts des conditions pédoclimatiques et du mode cultural sur la réponse du niébé (<i>Vigna unguiculata</i> L. Walp.) à l’inoculation endomycorhizienne avec <i>Rhizophagus irregularis</i>

Abstract: Impacts des conditions pédoclimatiques et du mode cultural sur la réponse du niébé à l'inoculation endomycorhizienne avec Rhizophagus irregularis 5466 de l'inoculation sur la croissance du niébé a été noté, attestant ainsi l'influence du mode cultural sur la réponse à l'inoculation endomycorhizienne. En culture pure, l'inoculation avec R. irregularis peut être une alternative pour améliorer la croissance et la productivité du niébé. Mots clés : Vigna unguiculata (L.) Walp, Rhizophagus irregularis, mode cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
2
3
0
1
Order By: Relevance
“…This positive effect observed during a mycorrhizal association on the biomass production of the aerial and the root parts, was earlier confirmed by Trouvelot et al (1982) on wheat. These results are in agreement with Diop et al (2013) ones who showed that the biomass production of vine was enhanced by mycorrhizal inoculation. Our results were also in accord with Zouari et al (2020) confirmations about rooting and growth of carob plants improvement by establishing a successful artificial symbiosis with P. tinctorius fungus species.…”
Section: Discussion Discussion Discussionsupporting
confidence: 93%
“…This positive effect observed during a mycorrhizal association on the biomass production of the aerial and the root parts, was earlier confirmed by Trouvelot et al (1982) on wheat. These results are in agreement with Diop et al (2013) ones who showed that the biomass production of vine was enhanced by mycorrhizal inoculation. Our results were also in accord with Zouari et al (2020) confirmations about rooting and growth of carob plants improvement by establishing a successful artificial symbiosis with P. tinctorius fungus species.…”
Section: Discussion Discussion Discussionsupporting
confidence: 93%
“…The improvement of KVX growth by inoculation could be the effect of the improvement of host plant hydro mineral nutrition. Our results are in accordance with those of Haro et al (2015), Diop et al (2013) and Zhu et al (2015) which showed that biomass production is enhanced by mycorrhizal inoculation. However, these mycorrhizal parameters are not proportional to the number of spores contained in each inoculum.…”
Section: Discussionsupporting
confidence: 92%
“…Des résultats analogues sont trouvés par Haro et al (2017) qui ont montré que l'inoculation mycorhizienne du niébé avec les inocula indigènes permet d'améliorer la production de biomasse et le rendement de la production graine de cette plante. Ces résultats sont en concordance avec ceux de Diop et al (2013) qui ont montré que la production de la biomasse de Vigna est améliorée par l'inoculation mycorhizienne. Des résultats analogues ont également été obtenus pour le trèfle inoculé avec G. mosseae (Khaled et al, 2003), pour Acacia nilotica et Acacia senegal inoculées avec un complexe mycorhizien de souches indigènes (Laminou Manzo et al, 2009) et pour le Robinier inoculé à R. irregularis et G. versiforme (Zhu et al, 2014).…”
Section: Discussionunclassified